Pneumothorax during Alectinib Treatment for a Uterine Inflammatory Myofibroblastic Tumor with Lung Metastasis - Chang-Ting Lin; Chen-Hsuan Wu; Hsuan-Ying Huang; Chien-Ting Liu (Journal of Cancer Research and Practice)
An inflammatory myofibroblastic tumor (IMT) is an uncommon sarcoma subtype with histopathological features, including inflammatory infiltrates. Anaplastic lymphoma kinase (ALK) gene rearrangement has been reported in half of the patients with IMTs; therefore, crizotinib, an ALK inhibitor, may achieve a response rate of 50% in these patients. We present a case with an initial diagnosis of uterine sarcoma and multiple lung metastases. After the failure of doxorubicin-based chemotherapy, revised pathology from a palliative hysterectomy revealed an IMT with ALK gene rearrangement. Treatment with alectinib achieved an excellent tumor response. The accurate differential diagnosis of uncommon sarcoma subtypes is crucial because a specific targeted therapy may considerably alter treatment outcomes.